2000
DOI: 10.1128/aem.66.6.2484-2490.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bifunctional Enzyme Fusion of Trehalose-6-Phosphate Synthetase and Trehalose-6-Phosphate Phosphatase of Escherichia coli

Abstract: To test the effect of the physical proximity of two enzymes catalyzing sequential reactions, a bifunctional fusion enzyme, TPSP, was constructed by fusing the Escherichia coli genes for trehalose-6-phosphate (T6P) synthetase (TPS) and trehalose-6-phosphate phosphatase (TPP). TPSP catalyzes the sequential reaction in which T6P is formed and then dephosphorylated, leading to the synthesis of trehalose. The fused chimeric gene was overexpressed in E. coli and purified to near homogeneity; its molecular weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 44 publications
9
58
0
Order By: Relevance
“…This fusion protein yielded an active bifunctional TPS and TPP enzyme with trehalose biosynthetic capacity and restored stress tolerance when expressed in yeast. A similar construct has been reported for the fusion of the E. coli otsA and otsB genes encoding TPS and TPP, respectively, which has both enzyme activities and synthesizes trehalose when expressed in bacteria (Seo et al 2000).…”
Section: Discussionmentioning
confidence: 84%
“…This fusion protein yielded an active bifunctional TPS and TPP enzyme with trehalose biosynthetic capacity and restored stress tolerance when expressed in yeast. A similar construct has been reported for the fusion of the E. coli otsA and otsB genes encoding TPS and TPP, respectively, which has both enzyme activities and synthesizes trehalose when expressed in bacteria (Seo et al 2000).…”
Section: Discussionmentioning
confidence: 84%
“…, respectively) are very high when compared to the values of TPS and TPP from E. coli (Seo et al 2000). Moreover, the Thermus enzymes have also lower K m values, meaning that these enzymes have higher catalytic efficiency, when compared to that from E. coli.…”
mentioning
confidence: 80%
“…examined have high thermo- Relative activity(%) stability, as would be expected (Koyama and Furukawa 1990;Wang et al 2003). The TPP from the mesophilic M. smegmatis, on the other hand, was completely inactivated after incubation for 0.5 min at 100°C (Klutts et al 2003), and a mixture of TPS/TPP from E. coli retained only 3% of the original activity after incubation at 50°C for 30 min (Seo et al 2000). The enhanced stability of enzymes at high temperature is the result of differences in specific amino acid composition (Vieille et al 1996).…”
mentioning
confidence: 99%
“…The C-terminal region of the Synechocystis SPS shows 42% identity to the Synechocystis SPP (Lunn et al, 2000) but lacks several of the conserved, active site residues and does not have SPP activity (Lunn et al, 1999). Seo et al (2000) expressed a fusion protein of the E. coli trehalose-P-synthase (TPS) and trehalose-phosphatase (TPP) and found that the chimeric protein had both TPS and TPP activities. TPS and TPP are functionally and structurally related to SPS and SPP, leading to the question of whether a single polypeptide can have both SPS and SPP activities.…”
Section: Expression Of a Chimeric Synechocystis Sps-spp Protein In Ementioning
confidence: 99%